Ford Model ""T"" car no. 2, winner of the trans-continental race from New York to Seattle arrival, Alaska Yukon Pacific Exposition, Seattle, June 1909. - Nowell, Frank H., 1864-1950 (1909)
One of two cars entered by the Ford Motor Company in the contest for M. Robert Guggenheim trophy. Driven by Bert Scott and C.J. Smith. M. Robert Guggenheim appears behind the steering column to the left; Henry Ford is to the right of the driver. PH Coll 727.778 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number